Study of the Influence of an Interceptor on the Resistance of the High-speed Vessels Using CFD - داؤد , هلا; نوار عباس, (Latakia University Journal -Engineering Sciences Series, 2022)
This study aims to determine the influence of an interceptor on the total resistance of high-speed vessels using CFD (Computational Fluid Dynamic). The URANS method and k-ω Shear Stress Transport (SST) model with ANSYS program were used to solve the Navier-Stokes equations. The Volume of Fluid method was used to capture the free surface and the interaction between the two phases (water, air) around the hull. The comparison between the CFD and Exp-results of total resistance shows a good agreement.